Development of the composition and technology of microcapsules of organoselenium compounds (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
This article presents the biological role of selenium in the body and its distribution in the environment, as well as the main microencapsulation methods, including extrusion, drying, emulsification, and ion gelation, and describes their applications in various fields. Cosmetic research is currently underway to develop these technologies, which guarantee improved quality and effectiveness of medicines, foods, and dietary supplements, which, in turn, positively impacts public health. The article presents the materials and methods of research, model compositions of microcapsules of potassium salt of selenistonimonic acid, preparation of models of microcapsules of potassium salt of selenistonimonic acid, Description of microcapsules in bulk and individually, description of microcapsules after drying, rationale for choosing the correct model composition of microcapsules, composition of microcapsules, A technological scheme for the production of microcapsules was developed based on the results of the study, an optimal composition of microcapsules of potassium salt of selenite-antimonytic acid and a technology for microcapsules using the extrusion method were developed, and a technological scheme for production was proposed.
Keywords: glutathione peroxidase (GPx) and iodothyronine deiodinase, triiodothyronine (T3), thyroxine (T4), microencapsulation, biologically active substances, pharmaceuticals, cosmetics, stability, bioavailability, technology